The importance of health and posyandu in increasing the potential of villages towards intelligent communities - Gulo, Hubari; Afifah, Muthia Rachma; Harahap, Putri Amelia; Khairiyah, Dina (Talenta Publisher, 2019)
In general, a woman, especially a mother, plays a very important role in family health. This happens because a mother tends to have greater attention to the health condition of her family. Mother's attention is very diverse ranging from implementing a healthy lifestyle, providing healthy and fresh food, cooking nutritious food, washing clothes, cleaning the house and many other things that are always done by a mother. Especially things related to family domestic work activities. With so many responsibilities and activities of a mother to maintain family health, sometimes makes her forget about her own health. Though the health of a mother is very important in maintaining and improving the quality of family health, both physical health such as hypertension and mental health. In conclusion, that the health program was held, began to open awareness and increase information on the importance of maintaining health,